Utilization of Okara as a Culture Medium by Membrane Concentration Process for High Oil Production by Oleaginous Yeast, Lipomyces starkeyi - Hiroya Taki; Kentaro Mine; Mana Miyamoto; Jiro Seto; Shinji Matsuo; Kazuo Kumagai; Hideto Matsuyama (Fermentation)
Palm oil, widely used in various products, poses environmental and climate change risks. “Yeast oil” produced by Lipomyces starkeyi, an oil-producing yeast, is one of the sustainable alternatives for palm oil and was successfully produced as an edible substitute for palm oil. However, the high cost of the culture medium for oil production remains a challenge for practical applications. Okara is a by-product of tofu and soymilk production. Because yeast extract contributes to the high cost of the culture medium, we considered using okara, a cheap and nitrogen-rich substitute, to reduce costs. In the initial study with okara, the production of yeast oil was confirmed, but its productivity was low due to the high viscosity caused by its insoluble solids. To overcome this, we extracted and concentrated nitrogen components in okara using the membrane concentration process. Using NF (nanofiltration) membrane concentration, oil production increased 1.69 and 1.44 times compared to the unconcentrated extract solution (added 90% (v/v) in the culture medium) and yeast extract (added 5% (w/v) in the culture medium), respectively. These findings indicate the potential for a significant cost reduction in the culture medium and high oil yield in yeast oil production.